Answer:
v=−27
Step-by-step explanation:
Since v is on the right side of the equation, switch the sides so it is on the left side of the equation.
−6(3v−4)+8v=4(v+7)
Simplify −6(3v−4)+8v
−10v+24=4(v+7)
Simplify 4(v+7).
−10v+24=4v+28
Move all terms containing v to the left side of the equation.
−14v+24=28
Move all terms not containing v to the right side of the equation.
−14v=4
Divide each term by −14 and simplify.
v=−27
The result can be shown in multiple forms.
Exact Form:
v=−27
Answer:
15.0
Step-by-step explanation:
Square root entire equation (-8 - 7)^2 + (-5 + 4)^2
Simplify the equation.
First, distribute the 2 in the left side of the equation.
Resulting in: 2x-6 = (x-1) + 7
Second, remove the parentheses form the right side of the equation (there is nothing to distribute there).
Resulting in: x - 1 + 7
Now simplify the right side of the equation by subtracting the 1 from the 7.
Resulting in: x + 6
Our goal is to isolate the x to the left side, and the numerals to the right side.
With that in mind, add the 6 (from the right side) to both sides. This cancels out the 6 on the right side.
Resulting in: 2x = 12
Lastly, in order to fully isolate the variable (x), we divide both sides by 2.
Resulting in: x = 6
Hope this helps.
Graph A because a graph of non proportional relationship will not pass through the origin (0,0) hope this helps! Remember to give me a like if it did please and thank you!
C aka y = -4.6 and y = 4.6
Step-by-step explanation:
i just took the unit review test on edg. :)